Biometria, taxa de eclosão e microbiota bacteriana e fúngica de ovos de jacaré-do-pantanal - Caiman yacare DAUDIN, 1802 - Pulcherio, Rachel de Sousa Lima (2012)
The commercial breeding of the Pantanal Caiman has been growing in the State of Mato Grosso through the breeding system named ranching, which means that the eggs are collected in the wild, they are artificially incubated and the hatchlings are reared in adequate rearing pens. Thus, one can observe that this economic activity is intimately dependent on the species reproductive efficiency in the wild and on the conditions the artificial incubation occurs. The hatch rates at crocodilian farming reflect the success of the artificial incubation, being directly related both to the conditions of the egg transportation and to the sanitary conditions of the incubator room. Taking into consideration the lack of information about the nests, about the eggs biometry, about the hatchlings, and about the composition of the bacterial and fungal microbiota of C. yacare meant to commercial breeding, this paper aimed at measuring the C. yacare nests, at counting the number of eggs per nest, at taking the biometry of eggs and of new born hatchlings, at checking the hatch rates, and at characterizing the bacterial and fungal microbiota of eggs at the moment of collection for artificial incubation. Twenty nests from four different areas – Piuval, Estrada Parque, Vazante and Lixeiro - of a farm in North Pantanal, in the town of Poconé were evaluated. The average height, width of the bottom and of the top of the nests were, respectively, 36.3 cm, 126.8 cm and 46.5 cm. From these 20 nests, there was a total of 464 eggs, with an average of 23.2 eggs per nest and hatch rate of 72.41% (336 eggs). Among the 128 eggs that did not hatch, 124 (96.9%) presented a fetid smell and a caseous/putrid content, and 4 (3.1%) had hatchlings with the yolk-sac unresorbed. The average values observed as for the length, the width and the mass of the eggs were, respectively, 6.6 cm, 3.9 cm and 67.5 g. The average values as for the snout-vent length and for the body mass of the new born hatchlings were, respectively, 12.2 cm and 45.1 g. The statistical analysis did not reveal relevant statistical differences (p>0.05) among the four regions, as for the parameters: sizes of the nests, hatch rates, number of infertile eggs, eggs that did not hatch (fetid smell or late development), number of eggs per nest, size of the eggs and of the hatchlings. In the 20 nests that were studied, 22 different bacteria were identified, and the most frequent were Bacillus cereus, Citrobacter freundii, Enterobacter aerogenes e Flavobacterium multivorum while the less frequent were Escherichia hermanni, Hafnia alvei, Morganella morganni, Salmonella sp., Shigella sonnei e Serratia marcescens. Seven different fungi were found, the Fusarium sp. being the most frequent and the Geotrichum sp., Mycelia sterilia and Trichoderma sp. the less frequent. All bacteria and fungi that were isolated at this study have already been related by other authors as part of the crocodilians oral and/or cloacal microbioat or as ethiological agents of infectious processes.